Effects of Lighting, Liquid Color, and Drink Container Type on Volume Perception. (October 2019) - Chen, Yi-Lang; Lee, Yi-Chien
This study explored the effects of geometric features (i.e., proportionate size and elongation) of tumblers and goblets on volume perception under different lighting environments and with different colors of liquid. Sixty individuals (30 men and 30 women) participated in an experiment that demonstrated volume perception of a specified amount (100 ml or 200 ml, depending on the container) by pouring water or red wine into different pairs of glasses. The results revealed the goblet and tumbler pairs in both the proportionate-size and elongation groups produced significant effects on overall volume perception; by contrast, the effects of lighting and liquid color were only observed in specific groups. The geometric features of the glasses yielded inconsistent results for different pairs of glasses; these dissimilar results may have been caused by differences in visual cues (glass rim or height) affecting volume perception under different experimental settings. In addition, this study revealed that men underestimated the volume more than women did and thus poured more liquid into the glasses. In practical application, these study results should be considered in conjunction with the context and purpose of drink and container selection to understand the commensurate illusory effects.